The Demerger Impact upon Sustainable Development of Economic Entities: Evidence from Romania - Baba Camelia Mirela; Duguleana Constantin; Dinca Marius Sorin; Duguleana Liliana; Dinca Gheorghita (Sustainability, 2021)
The Covid-19 induced economic crisis has significantly affected almost all businesses from nearly every sector, causing severe financial problems, lack of cash assets, and decrease of revenues. In this context, the economic entities were forced to look for adjustment and rescue solutions of their activities. One possible solution for the recovery and reorganization of economic entities' activities is demerger. This paper evaluates the impact of demerger upon the sustainable development of economic entities in terms of economic efficiency and financial performances. To achieve this goal, a statistical analysis of profitability ratios before and after the demerger, as well as a structural analysis of 268 demerger projects for the April 2012-April 2021 period, were performed. The results attest there are no significant differences between the ex-ante and ex-post financial performances. However, demerger seems to have a positive effect upon analyzed companies helping them to overcome economic hardships, rethink their business strategies, and continue their activity in the medium and long-term time horizon.
Keywords: sustainable development; financial performance; demerger restructuring